Rapid detection of Dirofilaria immitis in mosquito vectors and dogs using a real-time fluorescence resonance energy transfer PCR and melting curve analysis - Thanchomnang T. (2014)
A real-time fluorescence resonance energy transfer (FRET) PCR supplemented with melting curve analysis for the rapid molecular detection of Dirofilaria immitis in mosquito vectors and dog blood samples was developed. This real-time FRET PCR was based on the fluorescence melting curve analysis of a hybrid between an amplicon generated from the D. immitis ribosomal RNA gene sequence and specific fluorophore-labeled probes. The sensitivity, specificity, accuracy, and positive and negative predictive values of this method were all 100%. Besides being highly sensitive and specific, this PCR is fast and offers a high throughput. Therefore it is a suitable and powerful tool for the diagnosis and for epidemiological surveys of canine dirofilariasis as well as for molecular xenomonitoring of D. immitis in mosquito vectors. © 2009 Elsevier B.V. All rights reserved.